2012
DOI: 10.1016/j.asjsur.2012.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Surgical resection for hepatocellular carcinoma in pregnancy: A case report

Abstract: Hepatocellular carcinoma (HCC) occurring in pregnancy is very rare. The prognosis is usually poor because of unclear clinical presentation. A 30-year-old woman who suffered from HCC during pregnancy underwent hepatectomy twice, and resection for pulmonary metastasis once. A healthy infant was delivered after the first hepatectomy. Currently, she remains disease free 55 months after the second hepatectomy and 39 months after pulmonary metastatectomy. Moreover, she had another healthy infant 37 months after pulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Currently, repeat hepatectomy seems to be a better choice for recurrent HCC. However, no long-term survival after HCC recurrence during pregnancy has been reported in the literature [5]. Nonetheless, the present case survived without recurrence for approximately 2 years after the second hepatectomy for recurrent HCC and 5 years after the first hepatectomy.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Currently, repeat hepatectomy seems to be a better choice for recurrent HCC. However, no long-term survival after HCC recurrence during pregnancy has been reported in the literature [5]. Nonetheless, the present case survived without recurrence for approximately 2 years after the second hepatectomy for recurrent HCC and 5 years after the first hepatectomy.…”
Section: Discussionmentioning
confidence: 55%
“…HCC during pregnancy, which is believed to have a worse prognosis than that among non-pregnant woman, is extremely rare, with only 62 cases having been reported worldwide to date [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Accordingly, studies have shown an overall 6-month and 1-, 2-, and 3-year survival rates of 50%, 29.5%, 18.2%, and 13.6%, respectively, with a median survival of 18 months in pregnant patients with HCC [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Management during pregnancy may include hepatectomy 98,99 . Earlier diagnosis and active treatment have translated to modest improvements in survival for this small cohort 96 …”
Section: Specific Conditionsmentioning
confidence: 99%
“…It appears that the morbidity and mortality of HCC during pregnancy has improved over time as the diagnosis tended to be made earlier and patients tended to receive resection and other treatments. 6 El-Serat et al 7 reported that HCC were more aggressive with an overall one-year survival of only 23%. Pregnancy with HCC is believed to impart a worse prognosis than in non-pregnant women.…”
Section: Introductionmentioning
confidence: 99%